Penggunaan Metode Audiolingual dalam Maharah Istima' di MTs. KH. Hasyim Asy’ari Malang - Mufida, Chilma Munthia Syarul (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The research conducted by this researcher aims to find out 1) The use of the audiolingual method in maharah istima' at MTs. KH. Hasyim Asy'ari Malang 2) The steps of using the audiolingual method 3) The technique of using the audiolingual method 4) The advantages and disadvantages of the audiolingual method. The method used in this research is qualitative with research instruments in the form of interviews, observations, and documentation. As a result, 1) the use of the audiolingual method for listening skill aims so that students are able to understand speaker's speech correctly and well without feeling difficult 2) The steps for using the Audiolingual Method include presenting dialogue texts, students memorizing dialogues, presenting sentence patterns in dialogue, dramatize the dialogue, and the teacher asks students to compose sentences according to the sentence patterns in the dialogue 3) The technique used in the use of this method is listening to dialogue, memorizing dialogue, dictation, and connecting words 4) The advantage of this method is that students become proficient in forming patterns. sentences, have good and correct pronunciation, be active in dialogue, gain direct language experience while the drawback is that students tend to copy or imitate because they pay less attention to when learning takes place